EDUKASI PENANGANAN HIPERTENSI DAN PENGAPURAN BAGI LANSIA DI KELURAHAN MARTOBA PEMATANGSIANTAR - I Ngurah Gede Verar Fujastawan; Isa Harpika Br. Ginting; Jesicca Hasibuan (Yayasan Nusantara Hasana Berdikari, 2023)
This community service program aims to improve the understanding and management of hypertension and calcification problems among the elderly in Kelurahan Martoba, Pematangsiantar. The education program was conducted through interactive health talks, demonstrations of anthropometric and blood pressure measurements, and sessions on therapeutic exercise for hypertension. Evaluation was carried out using pre-test and post-test assessments to measure increased knowledge and changes in healthy lifestyle behaviors. The results demonstrated reductions in average systolic and diastolic blood pressures, enhanced understanding of healthy eating habits, and increased elderly participation in exercise routines aimed at strengthening bones and joints. This program proves that an educational and participatory approach can be an effective strategy in managing hypertension and calcification-related health issues among the elderly, thus fostering self-awareness regarding the importance of prevention through a healthy lifestyle.